Effects of technological, organizational, and environmental factors on social media adoption - Sikandar Ali, Qalati (My University, 2020)
Electronic commerce is becoming a significant hub for sourcing products/services which helps organizations to connect with potential customers and gain competitive advantages, though little empirical work focuses on small businesses operating in developing countries to date. Increasingly, companies are looking to utilize social media to connect with stakeholders and pursue several benefits. This study aims to investigate the technological, organizational, and environmental (TOE) factors that influence small- and medium-sized enterprises’ (SMEs) social media (SM) adoption in developing countries. This study used a closed-ended questionnaire to collect data from randomlyselected respondents (owners, executives, and managers) from SMEs in Pakistan. SMART PLS version 3.2.8 was used for path analysis of 316 responses and for structural equation modeling. The research findings include the direct influence of TOE factors (relative advantage, interactivity, visibility, top management support, and institutional pressure) on SMEs’ SM adoption, and in turn SM adoption also has a positive influence on SMEs performance. Moreover, the coefficient of determination of the study showed that 77.7% of the variation in SM adoption occurs because of TOE factors and 29.8% variation in SMEs occurred because of SM adoption. This paper has implications for practitioners and scholars interested in exploring the SM adoption and usage by SMEs.
JAFEB The Journal of Asian Finance, Economics and Bussines
Keywords: Small and medium-sized Enterprises; Developing countries; Social media adoption; Institutional pressure